Implementation of a Differentiated Approach to the Organization of Distance Learning - Kachalov, Dmitry V. (2020)
The widespread practice and results of the introduction of distance learning in several countries prove its economic efficiency. In this article, the authors consider the possibilities and advantages of using a differentiated approach in the practice of distance learning at a university. The article describes the pedagogical experience of structuring distance learning in the form of a new educational model - a block-modular system used by teachers in the practice of higher education. The authors argue that such structuring ensures the integrity of the perception and presentation of educational material, contributes to a better mastery of the discipline, provides the ability to build personal educational trajectories of students and identifies the following principles: flexibility, individualization, modularity, differentiated form of control..